Dynamic optical tweezers generation using a PANDA ring resonator - Punthawanunt, S.; Songmuang, S.; Mitatha, S.; Yupapin, P. P. (My University, 2011)
We propose a novel system of a tweezers generated source using a dark-bright soliton pulse propagating within a PANDA ring resonator, which is consisted of an add/drop optical multiplexer and two nanoring reonators. The potential well stability is generated and achieved when the system is controlled by the Gaussian pulse via a control port. The dynamic multi-tweezers can be generated, which can be available for molecule/atom trapping and transportation sources.
Keywords: Dynamic tweezers; Innovative Microring and Nanoring; Molecule/atom guide; Molecule/atom trapping